Comparing the pregnancy outcomes of cleavage and blastocyst stage in frozen embryo transfer cycles: A cross-sectional study - Zahra Parsafar; Razieh Dehghani-Firouzabadi (Shahid Sadoughi University of Medical Sciences, 2023)
Abstract Background: In vitro fertilization has advanced in many ways, and new techniques are challenging. Blastocyst transfer is an alternative method for embryo transfer (ET) to improve in vitro fertilization outcomes. Objective: The present study was performed to determine the effect of pregnancies resulting from ET in the blastocyst stage compared to the cleavage stage in frozen cycles to select a better method of assisted reproduction. Materials and Methods: This cross-sectional study was conducted on 194 women who referred to the Yazd Reproductive Sciences Institute, Yazd, Iran, between April 2019 and December 2020. They had a frozen ET as either cleavage or blastocyst (n = 97/each group). The study compared the pregnancy and fetal outcomes in the 2 groups of ET at the cleavage and blastocyst stages. Results: The results showed that the blastocyst stage group had higher levels of anti-Mullerian hormone, ovule number, 2 pronuclear number, and embryo number than the cleavage stage group. The frequency of chemical pregnancies was 52.6% and 36.1% in blastocyst and cleavage group respectively (p = 0.02). Also, the frequency of clinical pregnancies was 41.2% and 22.7% in blastocyst and cleavage group respectively (p < 0.001). No statistically significant difference was observed between 2 groups in abortion, preterm delivery, multiple births, preterm premature rupture of membranes, gestational diabetes and preeclampsia, ectopic pregnancy, neonatal hospitalization in Neonatal Intensive Care Unit, and fetal abnormalities (p > 0.05). Conclusion: The results showed that transmission in the blastocyst stage compared to the cleavage stage is associated with an increase in chemical and clinical pregnancy, while other pregnancy outcomes are the same in both groups.